Rare case of a cervical nodular adipose mass - Pinto, Ana; Suárez, Marisa; Scigliano, Horácio (Citotech Online - Case Review, 2017)
Cervical and supraclavicular adipose tissue masses are relatively rare, being lipoma and hibernoma the most e less frequent forms. The present paper deals with a case of a 72-year-old patient with clinical history of right supraclavicular nodular lipomatous mass, with cytological diagnosis of probable hibernoma. The histology of the surgical specimen confirmed the cytological suspicion.